Marketing Portugal as a destination through the film A Gaiola Dourada by Rúben Alves - Carvalho, Susan (2023)
The paper examines the destination marketing opportunities of film tourism through a case study of the Franco-Portuguese movie The Gilded Cage, partly set in the Douro region, in Portugal. The movie, directed by Ruben Alves, was a large box office success in various countries. With this being said, a content analysis was undertaken based on pre-developed categories drawing on discourse analysis of the characters’ statements, descriptions and information provided concerning Portugal and France, as tourism destinations, as well as the study of multimodal language and symbols through images presented. Regarding the predominance of visual communication identified in movies, Kress e van Leeuwen (2001; 2006) refer that this form of communication is another way of interpreting linguistic structures. Given the power of multimodal texts in the dissemination of images and representations of destinations/places, this paper also aims at analysing the audience, tourism markets, film genre, the 3 Ps of film tourism (place, performance and personality), places visited, icons, incorporation of the destinations with the script, the end credits, support provided and audience opinions. Thus, it was found that the film The Guilded Cage (2013) offers diverse destination marketing opportunities that could help increase the potential of the destinations’ visitor markets (Schofield, 2006).